Investigating Consumer Insight by Using Completion Techniques: A Pilot Study of a Motorcycle Accessory Shop in Thailand - Putthiwanit, Chutinon (International Review of Management and Marketing, 2012)
With almost ten percent of the world’s motorcycles in use in Thailand, this indicates that Thailand is a big market for motorcycle accessories in the world. This pilot qualitative research aims to investigate consumer insight by using completion techniques (sentence completion and story completion). Three respondents were deployed by using accidental sampling. Respondents were recruited to complete questionnaires when they entered the motorcycle accessory shop and were reported as male and at least 15 years old. This research was conducted in a motorcycle accessory shop in the Northeastern part of Thailand due to its prone to deal environment. From the results of the story completion tests, all participants agreed to take part in a promotion which gave a ten percent discount for membership card holders. They came to the motorcycle accessory shop by the recommendation of friends (positive Word-Of-Mouth). Moreover, consumers are satisfied when a seller can give them information or suggestions on motorcycle accessories as well as providing good after-sales service. Notwithstanding, this research is merely a pilot qualitative research, used as a guideline for future study in the motorcycle accessory market. Further research should increase the sample size in order to improve the validity of the research. Quantitative research is highly suggested when dealing with a few hundred or more accessory buyers. Keywords: Completion technique; Sentence completion; Story completion; Motorcycle; Motorcycle accessory; Motorcycle accessory shop JEL Classifications: M31; M39